Numerical Synopsis of the Phanerogamic Flora of the Valley of Mexico - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 1989)
Among the furnished information the following is outstanding. Out of 2071 wild species, recently recognized as members of the Phanerogamic Flora of the Valley of Mexico, 161 are introduced or probably introduced from distant regions, 522 belong to the Monocotyledoneae and 16 to the Gymnospermae. Mainly as a result of the exploratory effort, 37 undescribed species were discovered and 436 were determined as new records for the area, jointly with 75 genera and 6 families. In the present state of knowledge it can be estimated that 3 to 6% of the native flora has not yet been recorded. Best represented families are: Compositae (18.4%), Gramineae (11.7%) and Leguminosae (6.4%). More than 80% of the species are herbaceous plants, the trees represent less than 4%, the epiphytes ca. 1%, the climbers ca. 4%, aquatics and subaquatics 8.4%, parasite and “saprophytes” 1.4%, evident succulents 5.2% and halophytes 1.3%. In the process of the preparation of the Flora 66 authors participated, among which 6 works in foreign institutions and 45 participated as students. Lists of novelties registered as a consequence of the preparation of the flora are included.